Rancang Bangun Sistem Disposisi Surat Berbasis Web untuk Mendukung Transformasi Digital di BPS Kota Banjarmasin - Nindy Permatasari; Mifthahul Rahmi; Cahya Karima; Pramawahyudi Pramawahyudi; Afian Syafaadi; Sausan Hidayah Nova; Dwi Agung Wibowo; Nina Mia Aristi; Riska Kurnia; Muhammad Noor (Jurnal Nasional Teknologi dan Sistem Informasi, 2026)
The Central Bureau of Statistics (BPS) of Banjarmasin City faces challenges in managing incoming and outgoing correspondence, as the manual disposition process is time-consuming, paper-based, and prone to delays or document loss. To address these inefficiencies, a Web-Based Mail Disposition Application was developed to digitalize the document management process. The system allows users to record, track, and distribute correspondence efficiently through an integrated platform that supports automatic notifications and secure digital archiving. This study employs a descriptive qualitative approach, focusing on system design, implementation, and evaluation of its effectiveness in supporting administrative workflows. The results show that the web-based application significantly improves operational efficiency, reduces administrative errors, and enhances transparency and accountability in correspondence management. In conclusion, the adoption of digital document management systems contributes to optimizing work performance and supports the realization of effective, efficient, and environmentally friendly public services at BPS Banjarmasin.